Effect of ethanol blending with biodiesel on engine performance and exhaust emissions in a CI engine - Aydin, Hueseyin; Ilkilic, Cumali (Pergamon-Elsevier Science Ltd, 2010)
The use of biodiesel as an alternative diesel engine fuel is increasing rapidly. However, due to technical deficiencies, they are rarely used purely or with high percentages in unmodified diesel engines. Therefore, in this study, we used ethanol as an additive to research the possible use of higher percentages of biodiesel in an unmodified diesel engine. Commercial diesel fuel, 20% biodiesel and 80% diesel fuel, called here as B20, and 80% biodiesel and 20% ethanol, called here as BE20, were used in a single cylinder, four strokes direct injection diesel engine. The effect of test fuels on engine torque, power, brake specific fuel consumption, brake thermal efficiency, exhaust gas temperature, and CO, CO(2), NO(x) and SO(2) emissions was investigated. The experimental results showed that the performance of CI engine was improved with the use of the BE20 especially in comparison to B20. Besides, the exhaust emissions for BE20 were fairly reduced. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Diesel engine; Emissions; Alternative fuel; Biodiesel; Ethanol